Intercostal misplacement of a thoracic epidural catheter -A case report- - Kim, Young Bae (The Korean Society of Anesthesiologists, 2010)
Epidural block is useful for chronic pain and thoracic surgery. However, there are several complications, which include vessels or dural puncture, pleural puncture, misplacement of epidural catheter and trauma to the spinal cord. We report a case of intercostal misplacement of an epidural catheter in a 66-year-old patient who scheduled for left thoracotomy.